2015
DOI: 10.1093/brain/awv029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognosis of Alzheimer’s disease at the mild cognitive impairment stage

Abstract: Three sets of research criteria are available for diagnosis of Alzheimer's disease in subjects with mild cognitive impairment: the International Working Group-1, International Working Group-2, and National Institute of Aging-Alzheimer Association criteria. We compared the prevalence and prognosis of Alzheimer's disease at the mild cognitive impairment stage according to these criteria. Subjects with mild cognitive impairment (n = 1607), 766 of whom had both amyloid and neuronal injury markers, were recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
256
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 325 publications
(288 citation statements)
references
References 32 publications
18
256
1
13
Order By: Relevance
“…This position is also in line with published guidelines explicitly requiring the presence of neuronal injury markers to come to a conclusion of Bintermediate probability^or Bhigh probability^MCI/AD [46]. Furthermore, recently the validity of this approach has been further confirmed by a large retrospective multicentre study showing that, in the clinical setting, the combined use of both amyloid and neuronal injury markers offers the most accurate prognosis in MCI patients [47].…”
Section: Results Of the Cochrane Reviewsupporting
confidence: 68%
“…This position is also in line with published guidelines explicitly requiring the presence of neuronal injury markers to come to a conclusion of Bintermediate probability^or Bhigh probability^MCI/AD [46]. Furthermore, recently the validity of this approach has been further confirmed by a large retrospective multicentre study showing that, in the clinical setting, the combined use of both amyloid and neuronal injury markers offers the most accurate prognosis in MCI patients [47].…”
Section: Results Of the Cochrane Reviewsupporting
confidence: 68%
“…In accordance with this hypothesis of heterogeneity of MCI A-N+ etiologies, we found that among all MCI A-N+, only 20% were positive by both biomarkers, whereas they were 47% in the MCI A+N+ (supplementary Table S4). However, it has been also proposed that MCI A-N+ may reflect a proportion of AD individuals with subthreshold Aß SUVr (Vos et al, 2016(Vos et al, , 2015. We SUVr in MCI A-N+ classified using CSF Aβ 42 as amyloid biomarker (Wisse et al, 2015).…”
Section: Patients Positive For Neurodegeneration Only (Mci Snap)mentioning
confidence: 94%
“…In particular, MCI A+N-did not display alteration of the fornix, showing that even though fornix alterations have been described at the MCI stage, they are not present in all MCI patients (Madhavan et al, 2015;Metzler-Baddeley et al, 2012). term of conversion rate and cognitive deterioration, but discrepancies appear between studies (Caroli et al, 2015;Petersen et al, 2013;Vos et al, 2015;Wisse et al, 2015). Our study is consistent with this prior knowledge, showing that MCI A+N-white matter is less altered than MCI A+N+ but more altered than MCI A-N.…”
Section: Patients Positive For Amyloid Onlymentioning
confidence: 94%
See 1 more Smart Citation
“…In this frame, NIA-AA criteria relate the number of abnormal biomarkers to the likelihood that MCI is due to AD [2]. Although a prospective comparison between these two different approaches (IWG2 and NIA-AA) is still lacking, the validity of this NIA-AA model has been confirmed by a large retrospective multicenter study showing that, in the clinical setting, the combined use of both amyloid and neuronal injury markers offers the most accurate prognosis in MCI patients [5]. Similarly, in a recent survey, neurologists working in European Alzheimer's Disease Consortium Centres agreed that only a combination of amyloidosis and neuronal injury biomarkers is a strong indicator of an underlying AD [6].…”
mentioning
confidence: 99%